Celebration comments/Vierings kommentaar - Marie Poggenpoel (AOSIS, 2005)
Health SA Gesondheid is celebrating its tenth birthday. Initially only nursing research and overview articles were published in this journal. Opsomming Health SA Gesondheid vier 'n tiende verjaarsdag. Aanvanklik is slegs verpleegkundige navorsings-en oorsigsartikels gepubliseer in hierdie tydskrif. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.